Heterogeneous Oblate Primaries in Photo-gravitational CR5BP with Kite Configuration - Ansari, Abdullah A.; Kumar, Prashant; Alam, Mehtab (Journal of Nepal Mathematical Society, 2019)
This paper presents the investigation of the motion of infinitesimal body in the circular restricted five-body problem in which four bodies are taken as heterogeneous oblate spheroid with different densities in three layers and sources of radiation pressure. These four primaries are moving on the circumference of a circle and form a kite configuration. After evaluating the equations of motion and Jacobi-integral, we study the numerical part of the paper such as equilibria, zero-velocity curves and regions of motion. Finally, we examine the stability of the equilibria and observed that all the equilibria are unstable.